Understanding the moderating role of gender in physical activity enjoyment and mental well-being: evidence from university students’ campus recreation participation - Karakullukcu, Omur Fatih; Ayhan, Cihan; Guder, Ferhat; Talaghir, Laurentiu-Gabriel; Cosoreanu, Dumitru Marius; Bentea, Cristina Corina (Frontiers in Public Health, 2025)
BackgroundParticipation in physical activity is considered an important factor not only for individuals’ physical health but also for their psychological well-being. Developing physical activity habits, especially among university-aged individuals, plays a critical role in long-term health outcomes. In this context, the impact of physical activity enjoyment on individuals’ mental well-being has become a topic of interest. However, the moderating role of individual differences, particularly gender, in this relationship has not yet been sufficiently clarified. The purpose of this study was to examine the relationship between physical activity enjoyment and mental well-being among university students and to reveal the moderating effect of gender on this relationship.MethodThe research was conducted using a relational screening model. The study group consisted of 392 university students (261 male and 131 female; mean age = 22.95 ± 2.58) from Sakarya University of Applied Sciences who participated in campus recreation activities. Data were collected via a face-to-face survey using the Physical Activity Enjoyment Scale and the Mental Well-being Scale. Descriptive statistics, Pearson correlation analysis, and regression-based moderation analysis using PROCESS Macro Model 1 were used in the statistical analysis.ResultsThe level of enjoyment of physical activity was found to have a significant positive effect on mental well-being (r = 0.427, p = 0.001; F = 50.388, p < 0.001; R2 = 0.280). Moderation analysis further showed that gender significantly moderated this relationship (ΔR2 = 0.049; p < 0.001). The effect of enjoyment on mental well-being was significant for both males (β = 0.2693; S.E. = 0.0348; p < 0.001; 95% CI [0.2010, 0.3377]) and females (β = 0.7913; S.E. = 0.0949; p < 0.001; 95% CI [0.6047, 0.9780]), with the effect being stronger among females.ConclusionThe findings show that considering gender-sensitive approaches in physical activity programs to be implemented on university campuses has a potential impact on improving the psychological well-being of students.